Integrating Powerful Language Models Enhancing ChatGPT and Google BARD - Khan, Gul Sher Ali; Khan, Rehmat Ullah; Khan, Akbar; Ashraf, Muhammad; Azhar, Shanila; Ahmed, Zahoor (Spectrum of Engineering Sciences, 2025)
Recent advances in natural language processing have led to powerful large language models such as ChatGPT and Google's BARD. These models have complementary strengths - ChatGPT excels at fluent language generation while BARD specializes in language understanding. This paper explores integrating these models to create more capable conversational agents. The methodology involves using transformer architectures, transfer learning, and careful comparative evaluation. Experiments demonstrate that combining the benefits of both models leads to conversational agents that can produce coherent, contextually relevant responses while accurately comprehending user intent. However, challenges remain around bias, security, and responsible AI development. Further research into model integration strategies and ethical application is warranted.